O Estado à beira-mar. Estratégias burocráticas na formação do mercado imobiliário em Matosinhos Sul - o exemplo da Comissão de 1 de março de 1996 - Lemos, Tiago (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
The genesis of Matosinhos Sul, as a territorial, social and symbolic 'reality', is largely associated with the formation of a real estate market at its geographical scale. This article presents a sociological reading of what is argued to be the central actor in the organization of that space for real estate exchange: the State, in particular at the level of local government. In this context, this analysis will focus on a political-bureaucratic strategy put in place by the municipal executive, which allowed the start of the Matosinhos Sul transformation, by adjusting the regulations of the urbanization plans to the dispositions of real estate developers, but also of architects: a (proto) commission that took place on March 1, 1996. The purpose of this text is to show that the ‘flexibilization 'of building regulations was not a conquest of the private universe over the State, but a possibility granted by the State to the private universe.